Application of Semantic Image Generation Techniques Based Detail Preserving Image Method for Repoussé Craft (Journal of Fiber Bioengineering and Informatics, 2024)
Text-to-image technology is a technology for mapping target image sets through natural language andis the latest production method for new content. The repoussé craft1is ancient Chinese gold and silverfine art crafts. Although the craft has been studied, its exploration in digital research is relatively new.To modernise the repoussé craft, this paper takes the combination of 3D generated drawings of repoussé craft motifs with text-to-image technology as a research object, applies current artificial intelligenceto the study and analyses the possibilities of the combined application and related text specificationrecommendations, tests and analyses the impact of the changes in the prompt and weighted valuesettings on the repoussé craft jewelry design style. The results of the study show that the way theprompt2 and matting image weights are set plays a key role in the stabilisation of the imaging style.This study not only fills the gap in the combination of repoussé technology and AI technology but alsoplays a positive role in the stability of the style of the enhanced text to imaging, which provides a specificparameter basis and a new way of thinking for the future application of AI technology in the design offashion jewelry and even in the wider field of fashion design.